Review on IMC-based PID Controller Design Approach with Experimental Validations. Issue 3 (3rd April 2023) - Nath, Ujjwal Manikya; Dey, Chanchal; Mudi, Rajani K.
ABSTRACT: Internal model control (IMC) based proportional integral derivative (PID) controller design is found to be a well-explored topic over the last three decades. Possibly, this model-based controller design technique has got wide acceptance among process engineers due its simple tuning and clear functionality. Literature survey reveals that IMC has three important features, i.e . dual stability, perfect control, and zero offset. Another most interesting feature of IMC is that it has the sole tuning parameter, i.e. closed loop time constant ( λ ) which is required to be adjusted for achieving the desired closed loop response. Various guidelines for choosing the appropriate value of λ depending on the process characteristic and desired closed loop performance are provided in a good number of research findings. Especially, the design of the IMC controller for integrating and unstable processes is really a challenging task and hence widely explored by researchers. In this study, a brief review is provided on IMC-PID tuning for various classes of single input single output (SISO) processes along with a table containing their tuning relations. In addition, IMC controllers with adaptive, auto-tuning, and fractional-order structure have also been discussed here. However, in practice most of the industrial processes are multi input multi output (MIMO) in nature and hence, this review also includes significant discussions on IMC tuning strategies for MIMO processes. Real-time implementations of IMC techniques reported in the literature are also discussed. Finally, a comparative study is provided through real-time experimentation on a coupled tank system.